If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(y + 2) + 5 = y + 12 Reorder the terms: 3(2 + y) + 5 = y + 12 (2 * 3 + y * 3) + 5 = y + 12 (6 + 3y) + 5 = y + 12 Reorder the terms: 6 + 5 + 3y = y + 12 Combine like terms: 6 + 5 = 11 11 + 3y = y + 12 Reorder the terms: 11 + 3y = 12 + y Solving 11 + 3y = 12 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 11 + 3y + -1y = 12 + y + -1y Combine like terms: 3y + -1y = 2y 11 + 2y = 12 + y + -1y Combine like terms: y + -1y = 0 11 + 2y = 12 + 0 11 + 2y = 12 Add '-11' to each side of the equation. 11 + -11 + 2y = 12 + -11 Combine like terms: 11 + -11 = 0 0 + 2y = 12 + -11 2y = 12 + -11 Combine like terms: 12 + -11 = 1 2y = 1 Divide each side by '2'. y = 0.5 Simplifying y = 0.5
| 12x^2+20x=7x | | -17x-20=-13+80 | | -15x-20=-12x+115 | | 7(2x+9)-3=5(3x-2) | | 19-4x=13+2x | | 25x-20= | | 26-6x=15+5x | | 8x^3+56=0 | | x-0.1x=18000 | | 9t+7t= | | 7x-2=8x+4 | | 9(x+12)+3=-11(x-5) | | 7x+56=0 | | 9(x+13)-6=-3(x-5) | | 9(x+10)-6=-3(x-5) | | 5x+2=2x-4 | | 8x-12=13-9x | | 3x-15=15-2x | | 8x+11=6x+19 | | 7x^3-7x-7=0 | | (x-8)(4x-6)(8x-5)=0 | | 64^(x+8)=16x | | 7.50+1.00m=2.50 | | X+.25x=180 | | 100a^2+20a+1=0 | | 4x+x+50=180 | | 5y-6=45 | | X+50=x+50 | | 56=-3x+8 | | T^2=6t+11 | | 7x=-16-9x | | -2/3(6-2a)=6 |